PERANCANGAN ALAT PEMBERI PAKAN IKAN OTOMATIS BERBASIS MIKROKONTROLER - nata, david pra; Suharyanto, Cosmas Eko (Computer Science and Industrial Engineering, 2020)
Indonesia is an archipelagic country that has a lot of natural wealth and people who have a livelihood. The average public and private employee is a resident who lives in a busy or downtown area. Everyday city dwellers who are always busy with the hustle and bustle of the city and job descriptions that can make them feel bored certainly make them look for something they like to eliminate the boredom which is usually called a hobby. Hobbies themselves are fun activities that are usually done by someone to calm the mind and overcome boredom starting from doing sports, entertainment and other things. In this study the author will discuss hobbies related to entertainment that can be done by someone at home. Namely maintaining fish in the aquarium. In maintaining fish, fish that are kept in an aquarium cannot be carelessly cared for. Many things must be considered. Such as aquarium cleanliness, water content in the aquarium and when feeding the fish so that the fish do not die and harm the owner of the aquarium itself. With this problem, of course, aquarium owners need a schedule to take care of these things. For that we need a way how to feed fish automatically at predetermined times, namely by regulating the feeding time specified by the aquarium owner. With a 180º servo motor that is programmed with Arduino and DS3231, the microcontroller can process it so that the servo motor can rotate by following the schedule we specify.